RELEVANSI PEMIKIRAN EKONOMI ISLAM ABU YUSUF DENGAN MEKANISME PASAR MODERN - Haniatul Mukaromah; Fitra Rizal (Journal of Islamic Economics and Philanthropy, 2021)
Market mechanism is the most important thing in determining the price level in the market. This research aims to see how the market mechanism relevance according to Abu Yusuf with modern market mechanisms. The research method used is a qualitative research methodology with a library research approach. The results showed that there is a relevance of Abu Yusuf's Islamic economic thought with modern economics. This means that there are similarities between the concept of the market mechanism according to Abu Yusuf and the modern market mechanism. Abu Yusuf opposes government intervention in setting prices. The government acts as a regulator / referee in the market mechanism. This means that the government has the duty to ensure that prices in effect in the market are fair prices, which are obtained from natural market mechanisms (based on levels of demand and supply), not monopoly or market engineering. However, the government may intervene in price when there is a monopoly or market distortion.